Literasi Media Televisi Kepada Ibu Rumah Tangga dalam Pendampingan Menonton Anak - Lisahidah, Aulia; Fitriawati, Diny; Hasim, Hasim; Taufik, Cevi Mochamad (Universitas Brawijaya, 2024)
Abstract: The development of media is now increasingly rapid, information, entertainment and so on are increasingly accessible. However, in this digital era, television media still exists and is still quite popular with the public. The influence of television shows can be seen in children, one of them is early childhood where they can get new vocabulary from the shows they watch. with the right assistance, of course, this will have a positive impact on children. Assistance can also be done if parents, especially mothers, understand the importance of media literacy. The purpose of this research is to find out the knowledge of housewives in Cisumur Village about why mentoring children when watching television is very important, then how the mentoring process is carried out. The method used in this research is a descriptive qualitative approach. The descriptive qualitative approach is intended to reveal and describe how media literacy is helpful in selecting television programs for housewives. The results of this study indicate that the knowledge of housewives about why it is important to accompany children when watching television is quite good, and can practice or realize this knowledge so that there is a mentoring process carried out. However, mothers have not been able to make rules for viewing schedules, so that many of their children whose daily lives are only occupied with watching television.